SISTEM PEMUTUSAN HUBUNGAN KERJA PASCA BERLAKUNYA UNDANG-UNDANG CIPTA KERJA - Sasmita Ahmad Isan; Abraham Ferry Rosando (Gapenas Publisher, 2022)
The enforcement of labor law in Indonesia is certainly a very very interesting discourse to discuss, this is with the enactment of Law Number 11 of 2020 concerning Job Creation which has deleted, added, and changed some of the Articles in Law Number 13 of 2003 concerning Manpower. In fact, it has brought juridical implications for debate by a number of circles, because it not only invites practical problems, but also theoretic. termination of employment, to the obligation to negotiate after termination of employment. Second, the work copyright law has provided a demarcation line between the reasons for termination of employment, prohibitions on termination of employment, and the amount of rights in the form of severance pay, service award and compensation for rights that must be received due to termination of employment. , including the amount of rights due to termination of employment in Law no. 13 of 2003 concerning Manpower is much larger than Law no. 11 of 2020 concerning Job Creation